All for one and one for all: accommodating an extra electron in C60 - Klaiman, Shachar; Gromov, Evgeniy; Cederbaum, Lorenz S. (Physical chemistry, chemical physics, 2014)
Much like the neutral C60 fullerene, the C60− anion possesses certain unique properties which have attracted a great deal of research. One of these special properties, only recently fully uncovered, is that the C60− anion supports a substantial number of electronically stable excited states in contrast to other molecular anions with comparable electron affinity. In this work, we clarify how the C60− anion can support so many stable states by analyzing the radial and angular distributions of the excess electron bound to the anion. The analysis is based on ab initio calculations which are by far the most accurate on the C60− anion to date. Surprisingly, the radial distributions are highly similar for states of very different binding energies and the analysis stresses the importance of angular correlation in binding the excess electron. We further analyze the effect of the single excess electron on the electrons of the underlying neutral molecule. We demonstrate how this substantially modifies the actual distribution of the excess charge by shifting the underlying electron density. Implications of these findings are discussed.